Internacionalização como factor de valorização do capital intelectual. Um caso de estudo - Pousa, José Marcelino (2001)
O conhecimento é hoje reconhecido como um activo das organizações, como tal merece a atenção da gestão, não é por certo esta a principal preocupação dos gestores da maioria das empresas Portuguesas. O facto de o autor acreditar no que atrás se afirmou e trabalhar numa organização singular no contexto português, que tem como campo de actuação o mercado das telecomunicações e multimédia e que reconhece nos seus colaboradores o seu maior activo, criou a motivação para o estudo. O estudo tem como objectivo a análise de como é que a participação em programas internacionais de investigação e desenvolvimento (IST Information Society Technologies e EURESCOM European Institute for Research and Strategic Studies in Telecommunications) contribuiu para a valorização do capital intelectual. Os resultados mostram uma clara valorização do capital humano da organização, porque o programa resultou na participação num número considerável de projectos envolvendo um grande número de colaboradores, mas alguma debilidade na passagem de conhecimento tácito a explícito. Será portanto, um bom investimento a adopção de metodologias de gestão do conhecimento que o permitam monitorizar e avaliar. Sem dúvida que estas ferramentas permitirão identificar e recuperar o conhecimento existente, bem como garantir uma melhor captura no futuro. *** Abstract - The knowledge is today recognized as an important asset in the modern organizations, so it justifies the attention devoted by the management to the topic. But for sure this is not the main matter of concerns in the major part of the Portuguese companies. The author of the study believes in the importance of the knowledge for the organizations, and the importance of their management. Because he is working in a research and development organization unique in the Portuguese context, working in the field telecommunications and multimedia, where the workers are recognized as the main asset, motivate the author for Chis study. The main objective of the study is the analysis of how the participation in the research and development programs, running at international level under the scope of (IST Information Society Technologies e EURESCOM European Institute for Research and Strategic Studies in Telecommunications) contributed to increase the intellectual capital. The results show a clear increase of human capital in the organization, because a large number of workers had the opportunity to participate in projects developing work in the most advanced fields of telecommunication engineering. But some weaknesses were identified in the study, manly regarding aspects of transference of tacit knowledge to explicit knowledge. In conclusion, the adoption of tools that make possible the identification, evaluation and monitoring of knowledge in the organization is for sure a good investment. We believe that the deployment of such tools will allow the organization to find and recover part of the existing knowledge, as well as guaranty for the future a maximum efficiency in the structural capital creation.